Upaya Peningkatan Pengetahuan Masyarakat Mengenai Pendidikan Kesehatan Pendidikan Hidup Bersih dengan Mengelola Sampah - Syamsul, Tri Damayanty; Lala, Lala; Karim, Kasmawati (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2025)
Waste is a consequence of all human activities. If there is no community ability to manage waste, waste can cause environmental problems. The methods used are face-to-face counseling, lectures, powerpoints, leaflets, questions and answers, and discussions about sexual violence. The activity can run well and smoothly and the response of cadres and residents is very good. The community feels that as citizens, the community can know or understand about sexual violence and how to prevent it. To collect data and information in the study, the methods used are surveys, observations, and questionnaire distribution. Results: Preliminary findings show a significant improvement in public understanding of health education principles and clean living practices. Participants showed increased awareness of the importance of proper waste management and demonstrated better waste sorting practices. Educational interventions have succeeded in increasing public knowledge about health education and clean living. Ongoing efforts and further education are recommended to maintain and build on these improvements, ensuring long-term benefits to public health and environmental management in Kampung Baru Village.